Conservation status of the Italian flora under the 92/43/EEC 'Habitats' Directive. (2nd November 2021) - Fenu, Giuseppe; Siniscalco, Consolata; Bacchetta, Gianluigi; Cogoni, Donatella; Pinna, Maria Silvia; Sarigu, Marco; Abeli, Thomas; Barni, Elena; Bartolucci, Fabrizio; Bouvet, Daniela; Cogoni, Annalena; Conti, Fabio; et al.
Abstract: The results of the 4th National Report for the Italian flora under the 92/43/EEC 'Habitats' Directive are presented. The outcomes showed a general negative conservation status for plant species, with the worst situation being in the Mediterranean bioregion. At the National level, significant monitoring and conservation activities are required.